Mastery of Spanish morphology and syntax through e-learning among Malaysian students - Mohd Nor, Mariyati; Ismail, Radhiah; Husain, Salina; Mat Zin, Harnani (Universiti Malaysia Sarawak, 2024)
This study explores the usage of e-learning via an interactive blog in assisting student’s morphology mastery and sentence construction in the Spanish language. Data presented in this study were gathered through 1) interviews with fifteen (15) students between 20 and 23 years old, who were registered in Spanish Communication Level 1 at Sultan Idris Education University, Malaysia, 2) questionnaire involving 45 students about the effectiveness of the blog as an e-learning platform, and 3) analysis of writing activities and evaluations in the blog and the classroom. The data were analysed using the descriptive-qualitative approach and supported by quantitative data. The findings indicated that the blog was viewed positively as a learning platform that provided out-of-classroom opportunities to learn the Spanish language. The usage of the blog helped elevate students’ knowledge in mastering vocabulary, understanding the grammar system, and constructing grammatical sentences. The findings can guide Spanish language instructors in preparing suitable and attractive teaching and e-learning activities that contribute towards the understanding and proficiency of students learning Spanish as a foreign language.